Epidemiological investigation into an outbreack of gastroenteritis - Baldissera, Romeo Luiz; Meneghel, Stela Nazareth (Revista de Saúde Pública, 1986)
An epidemiological investigation into an outbreak of gastroenteritis on a ship anchored in Rio Grande harbor was reported. One hundred and eighty four personns acquired the disease, with an attack rate of 72,7%. The cases accurred one day after the beginning of te trip and the clinical manifestations were fever, malaise, headache, nausea, vomiting and diarrhea. There were no deaths. Three hypotesis were formulated to explain the etiology: typhoid fever, insecticide intoxication, and food related disease. Alimentary enquiries showed high attack rates for some foods eaten at dinner on Sunday December 3rd. Laboratory tests were performed: Widal reaction, haemoculture, coproculture, food analysis and analysis of water from the ship's fresh water tanks. Salmonella serotype "emek" was found in 40.1% of the samples. The bacteriological analysis of the water showed proved it unfit for human consumption. The alimentary etiology, in the light of the clinical, epidemiological and laboratorial data, was confirmed. It was impossible to establish the transmission vehicle. Water and some food remained under suspicion.